Boosting photoelectrochemical and photocatalytic performances of electronspun WO3 nanofibers by combining with biphase-Ag2WO4. (December 2020) - Cui, Yongping; Shang, Yaru; Shi, Ruixia; Wang, Yingzi; Zhu, Yuanna; Yang, Ping
Abstract: A novel biphase silver tungstate (Ag2 WO4 )/tungstate oxide (WO3 ) photocatalyst was synthesized through electrospinning process combined with a facile solid chemical reaction. The X-ray diffraction patterns, energy dispersive spectroscopy and Fourier transform infrared spectroscopy demonstrated that the photocatalyst is composed of monoclinic WO3, β-Ag2 WO4 and γ-Ag2 WO4 . The Ag2 WO4 /WO3 can completely degrade the rhodamine B (RhB) within 20 min under 300 W xenon lamp. The first-order kinetics constant k of Ag2 WO4 /WO3 is 26.3 times of WO3 . The recycling photocatalytic tests proclaimed that the Ag2 WO4 /WO3 is relatively stable. The composites possess smaller impedance and higher photocurrent intensity, which displayed the promoted photoelectrochemical activities. The broadened light harvesting and accelerated photogenerated charge carrier migration account well for the enhanced photocatalytic performance of the composite. The direct Z-scheme photocatalytic mechanism should be responsible for the boosted photocatalytic performances of biphase Ag2 WO4 /WO3 . This work gave new insights into the design and construction of WO3 -based direct Z-scheme photocatalysts. Highlights: Biphase Ag2 WO4 /WO3 was fabricated by electrospinning and solid chemical reaction. The Ag2 WO4 /WO3 is composed of monoclinic WO3, β- Ag2 WO4 and γ-Ag2 WO4 . The Ag2 WO4 /WO3 displayed the promoted photoelectrochemical activities. Ag2 WO4 /WO3 can completely degrade the RhB within 20 min. Z-scheme photocatalytic mechanism should be responsible for the boosted properties.